Role of interleukin-6 to differentiate sepsis from non-infectious systemic inflammatory response syndrome. (December 2016) - Ma, Li; Zhang, Hui; Yin, Yan-ling; Guo, Wen-zhi; Ma, Ya-qun; Wang, Yu-bo; Shu, Cheng; Dong, Lian-qiang
Highlights: IL-6 test has moderate diagnostic performance in differentiating sepsis from non-infectious SIRS in adults. IL-6 and PCT test has similar diagnostic value but higher than CRP. IL-6 might be specific, but not sensitive in differentiating sepsis from non-infectious SIRS. Abstract: Differentiating between sepsis and non-infectious systemic inflammatory response syndrome (SIRS) poses a great challenge. Several potential bloodstream biomarkers including Interleukin 6 (IL-6) have been investigated for their ability to diagnose sepsis. We conducted the present meta-analysis to evaluate the diagnostic quality of IL-6 in differentiating sepsis from non-infectious SIRS in adults. We also compared its accuracy with procalcitonin (PCT) and C-reactive protein (CRP). PubMed and EMBASE were systematically searched for studies published up to January 18, 2016. Twenty articles containing 22 studies and 2680 critically ill patients were included, of which, 21 studies also involved PCT and 14 involved CRP. Quantitative synthesis of studies showed that the pooled sensitivity/specificity of IL-6 and PCT were 0.68/0.73 and 0.78/0.67. The area under the curve (AUC) of IL-6, PCT and CPR for diagnosis of sepsis was 0.80, 0.83, and 0.71, respectively. This meta-analysis provides evidence that the IL-6 test has moderate diagnostic performance in differentiating sepsis from non-infectious SIRS in adults. IL-6 and PCT test has similar diagnostic value but higher than CRP. Considering its relatively high specificity, we recommend the use of IL-6 as a diagnostic aid to confirm infection rather than exclude infection in patients with SIRS.